To the question on convergence of the sums of the random step processes to a Poisson process - Grigelionis, B. (Lithuanian Mathematical Journal, 1966)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Б. Григелионис, К вопросу о сходимости сумм ступенчатых случайных процессов к пуассоновскомуB. Grigelionis, Laiptuotų atsitiktinių procesų sumų konvergencijos į Puasono procesą klausimu